PENERAPAN MODEL PEMBELAJARAN CONTEKTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 005 SEDINGINAN KECAMATAN TANAH PUTIH - Sari, Melda; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the students achievement of social studies SD Negeri 005 Sedinginan fourth graderes still low with an average value of 62,25 and minimum completeness criteria (KKM) social studies is 70. Between students, amounting to 20 people only 7 students who achieve classical KKM with 35%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of social studies class III at SDN 005 Sedinginan with implementation of learning model CTL. Formulation of the problem : Is the implementation of learning model CTL can improve students achievement of social studies at SDN 005 Sedinginan. The research was conducted on March 17, 2015 to April 16, 2015 by 2 cycles. Subjects were students of SDN 005 Sedinginan, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 62,25. in the first cycle improve an average 73,25 and an improve in the second with an average of 86,25. Activities of the teacher in the learning process in cycle of 58,33% and the second meeting improve 77,78%. Cycle II first meeting and the second meeting improve 80,55% and the second meeting improve 86,11%. Results of data analysis of students activities in the first cycle with the first meeting of an average 55,55% and a second meeting improve to 75% . Cycle II first meeting improve 77,77% and the second meeting improve to 86,11%. Resultsin the class III at SDN 005 Sedinginan that the implementation of learning model CTL can improve student achievement of social studies at fourth graderes SDN 005 Sedinginan.Key Words : implementation of learning model Contextual Teaching and Learning (CTL),